Distribution and sources of microplastics in the Beibu Gulf using in-situ filtration technique. (March 2023) - Zhu, Zuhao; Hossain, Kazi Belayet; Wei, Huihua; Jia, Renming; Gao, Xiaofeng; Jin, Haiyan; Cai, Minggang
Abstract: The Beibu Gulf is a vital link between China and the ASEAN nations, and microplastic contamination is rising due to fast growth, coastal life, fisheries, and mariculture. The abundance, distribution, and source analyses were conducted at 25 sample points for this study. According to this study, the average MPs was 0.25 ± 0.05 items/m 3, ranging from 0.01 items/m 3 to 0.89 items/m 3 . Fibers, white, cellulose, and 0.33–1 mm were abundant in shape, color, composition, and size, respectively. Multi-statistics-based source analysis indicated land-based inputs (packing materials, textile materials, fisheries, and mariculture) were dominant in the Beibu Gulf. In this study, we also acknowledged a comprehensive comparison and convenience between plankton pumps and other conventional designs to collect microplastic samples from water. We suggested that using a uniform design could elevate the data quality of microplastics. Highlights: The average abundance of microplastics was 0.25 ± 0.05 items/m 3 . The north of Beibu Gulf had a higher abundance of about 0.41 ± 0.28 items/m 3 . Packing, textile, fisheries, and mariculture were dominant sources. Plankton pump is more convenient than other designs for microplastic sampling. Smaller volumes of water could give a false interpretation of MPs abundance.